In‐Solution Structural Considerations by 1H NMR and Solid‐State Thermal Properties of Inulin‐d‐α‐Tocopherol Succinate (INVITE) Micelles as Drug Delivery Systems for Hydrophobic Drugs. Issue 21 (29th August 2014) - Catenacci, Laura; Mandracchia, Delia; Sorrenti, Milena; Colombo, Lino; Serra, Massimo; Tripodo, Giuseppe
<x xml:space="preserve">Abstract</x> 1H NMR is a suitable method to clarify the kind of interactions leading to the self‐assembly of amphiphilic polymers. This work shows, from 1H NMR studies performed in solution, that the self‐assembly ability of the synthesized Inulin‐d‐α‐tocopherol succinate (INVITE) amphiphilic polymers, can be addressed to specific π–π interactions between the aromatic regions of d‐α‐tocopherol. This result suggests the use of INVITE systems for the preferential loading of aromatic group bearing drugs such as curcumin. The preparation conditions, effect of drug loading, and lyophilization on the INVITE systems are evaluated by DSC and thermogravimetric analysis (TGA) analysis to assess whether common pharmaceutical processes could influence the physical properties of the amphiphilic polymers, such as crystallinity, glass‐transition temperature or thermal degradation, to predict the physical stability of the systems upon administration. Furthermore, the size stability of the micelle systems up to 60 days is monitored to assess the feasibility of the INVITE micelles' long‐term storage upon reconstitution with water. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>